Constructing your 2011 agenda. (New York McKinsey & Company, 2011)
Insights on the three priorities that reflect the diversity of issues companies are dealing with in these still uncertain times: pressure testing a company's strategy, boosting the flexibility of the supply chain, and enhancing personal productivity.
Keywords: Management; Business--Innovation; Economic indicators.; Business; Finance; Economics; Corporate sustainability; Knowledge management; Decision making; Organisational learning; Globalization - Economic aspects